NILAI KARAKTER DALAM CERITA RAKYAT YONOKHONG (KWADEWARE) DISTRIK WAIBU KABUPATEN JAYAPURA - Siswanto dan Asmabuasappe NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This research entitle Character Values in Cerita Rakyat Yonokhong (Kwadeware) Distrik Waibu Kabupaten Jayapura. The  purpose  of  this  research  was  to  describe  and explain  the  characters  values  contained  in the Cerita Rakyat Yonokhong (Kwadeware) Distrik Waibu Kabupaten Jayapura. The character values described and explained include: carefully, never give up, be responsible, wise, brave to admit mistakes, assertive, polite, sincere, love of country, working together, brave, affectionate, obedient, alert, smart, honest, united, independent, strong, believe in supernatural powers, meticulous, and rely on supernatural powers.  This research used a  qualitative descriptive  approach. The data in this research are the values  of characters that comes from Cerita Rakyat Yonokhong (Kwadeware).